Intestinal carriage of yeasts by children in hospitalar setting - C., Talarico (Revista do Instituto Adolfo Lutz, 2004)
At the last decades the nosocomial infections caused by yeasts raised significantly especially by Candida yeasts. The infections source can be endogen or exogenous, since spores of unicellular and multicellular are kept viable for months and several yeasts species are found in skin and mucosa of healthy people. In a saprophytic state yeasts are found in the human gastrointestinal tract but the relationship between the presence of these microorganisms and their pathology is associated with several facts such as: number, variety of sites colonized, effective use of antibiotics, associated infections caused by another microorganisms and mainly disturbance due to lack of immunity and metabolic. Yeasts in the gastrointestinal tract can be transmitted fecal-oral direct or indirectly from an individual to another. The transmission of a strain in a saprophytic state to a host can result in colony followed by infection. The infection can be serious depending on the host conditions and the etiologic agent that includes virulent factor and resistance to antifungal drugs. These attributes are important to Candida albicans in which enzymes with phospholipase activity are responsible for virulent factors. Resistance phenotypes, otherwise it should occur more frequently in non-albicans species. Concerning the possibility of an endogen disease and the spread of virulent and resistant strains, from the gastrointestinal colony, studies that contribute to determine these agents that constitute the microbiota of patients, are important to know the natural story of nosocomial infections caused by yeasts. This work aims at evaluating the intestinal tract as a source of hospital infections by yeasts describing the remaining species in the first hours and a possible change depending on the time that may happen to virulent phenotypic and resistance to ant fungi. Two hundred eighty one yeast samples from sixty-six children attended in pediatric and semi-intensive units in 2 public hospitals located in São Paulo and Guarulhos cities in Brazil were analyzed. The fecal samples were collected at the first hours after and during their arrival at the hospital. To identify the yeasts according to their gender and species traditional methods were used, analyzing morphological and physiological aspects. The ability to produce enzymes phospholipase and proteinase was verified the same way it was proposed by Price et al.1982 and Ruchel et al.1982. The sensibility to antifungals: amphotericin B (AMB), fluconazole (FZ), ketoconazole (CZ) e nistatin (NIS), was analyzed by the diffusion technical by disks (CECON São Paulo, Brazil). Resistant samples or with intermediate sensibility were confirmed by micro-dilution method according to NCCLS (1997) modified by EUCAST (2002). The isolated species were: Candida tropicalis (30%), C.parapsilosis (27%), C.krusei (4%), Trichosporon cutaneum e T.inkin (3%), Rhodotorula mucilaginosa e R.glutinis (2%), C.guilliermondii (2%), C.glabrata (1%) and C.kefyr (1%). Enzymatic activity was verified in most of the 84 C.albicans samples being 96% of phosfolipase and 95% of proteinase production. Among the non-albicans species of Candida it was observed 97% of phospholipase and 67% of proteinase activity. Less sensitive samples to azoic drugs including resistant or SDD sensibility, which depends on the achieved dose, were found in 4.3% of the 281 samples of yeast. The hugest percentage was observed in C.krusei (90%). We can conclude that different yeast species occur in stools of pediatric population hospitalized, including virulent strains and antifungal resistant phenotypes. The persistent of these phenotypes in the intestinal tract during hospitalization period may represents a risk factor contributing to endogen infection, or play a role in dissemination of potential pathogens inside a nosocomial evironment.